The State as Social Insurer, Labour Supply and Investments in Human Capital - Thomas Eichner (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
In this paper the welfare state is considered as insurance device. Redistributive taxation reduces the variance of life- time risk. Behind a veil of ignorance with regard to future position in society, agents decide in a two-parametric expectation/standard deviation-approach about labour supply and investment effort in human capital. Assuming DARA and see-through of agents, that means that they take the government's actions into account, it is shown that labour supply rises in dependence of increasing tax rates when investments are exogenous, and that investments rise in dependence of increasing tax rates when labour supply is exogenous. If investments and labour supply are free eligible, the adjustment of labour supply to fiscal tax changes is ambiguous. Redistributive taxation induces in any case individuals to invest successively more in human capital. Furthermore, fiscal policy effects on national income, income inequality and welfare are studied, and the constitutional chosen redistribution scheme is determined.
Keywords: 330